2024
DOI: 10.18517/ijaseit.14.1.17489
|View full text |Cite
|
Sign up to set email alerts
|

Biomass: A Versatile Resource for Biofuel, Industrial, and Environmental Solution

Van Giao Nguyen,
Minh Ho Tran,
Prabhu Paramasivam
et al.

Abstract: Biomass, noted for its adaptability, has various applications in biofuel generation, industrial use, and environmental cleaning. This study looks into the multiple roles of biomass as a renewable energy source, with a particular emphasis on its vital contribution to biofuel production. Through a thorough evaluation of different conversion routes—thermal, biological, and physical—the study emphasizes thermochemical processes' efficiency, cost-effectiveness, and adaptability. Notably, technologies like gasificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 222 publications
0
3
0
Order By: Relevance
“…The principal hubs in the marine transportation network are seaports, sometimes called ports, which are connected by shipping lanes. Comparably, ports in the modern conception of the global supply chain have developed from traditional hubs for loading, unloading, and storing goods to significant nodes that coordinate the whole supply chain [6], [7]. As demonstrated by the emergence of the container idea, which unifies international trade and fosters linkages between diverse modes of transportation, this expansion has dramatically raised port demand in the past few decades [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The principal hubs in the marine transportation network are seaports, sometimes called ports, which are connected by shipping lanes. Comparably, ports in the modern conception of the global supply chain have developed from traditional hubs for loading, unloading, and storing goods to significant nodes that coordinate the whole supply chain [6], [7]. As demonstrated by the emergence of the container idea, which unifies international trade and fosters linkages between diverse modes of transportation, this expansion has dramatically raised port demand in the past few decades [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, WtE technologies will address the urgent need for effective waste management solutions, playing an important role in the transition to a sustainable energy environment. It does this by providing renewable energy and at the same time meeting the demand for waste management solutions [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…Their primary objective is to create technology that is both capable of self-regeneration and has no negative impact on the environment. Extensive research has demonstrated that biodiesel, bioethanol, and biogas are superior to fossil fuels in terms of energy production (Cherwoo et al, 2023;Nguyen et al, 2024;Priya et al, 2022). Biodiesel, which is also known as fatty acid methyl ester, has been utilized as a viable alternative to fossil fuels for a considerable amount of time (Jeyakumar et al, 2023;Raheman and Padhee, 2014;Yuvenda et al, 2022).…”
mentioning
confidence: 99%